Vaccination of goats with Laser radiated Dictyocaulus filaria larvae - G, AL- Samarrae , S.A.; K., AL- Mashhadani, F. J. (The Iraqi Journal of Veterinary Medicine, 2001)
Irradiated D. filaria 3rd stage larvae with cantinuous emission of visible Helium- Neon Laser of ImW and a wave length of ( 632.8 ) nm. for three different exposure times of 5 , 10 and 15 minutes were used to vaccinate three groups of kids of five each at double immunization doses orally. The first dose contained ( 1000 ) larvae and the second was ( 2000 ) larvae at an interval of ( 4 ) weeks between then . After ( 5 ) weeks a challenge dose of ( 100 ) larvae per kg. Body weight ( non irradiated ) was given to all the groups in addition to a control group ( 4th ) of ( 5 ) kids . All animals were slaughtered after ( 6 ) weeks post-challenge. Results showed that the attenuated larvae at ( 5 ) minutes exposure to Laser irradiation was the most appropriate one and can be used as an attenuated irradiated larval vaccine effectively and safely. The assessment was based on clinical signs, body weight gains ,eosinophil counts of blood, fecal larval counts , mean worm burden and female sexual maturity, and gross pathological changes including lung lesion scores.